Rotatory Shortcut Tree Routing In ZigBee Networks - Durga Prasad, N; Sai Ganesh, D (International Journal of Computer Sciences and Engineering, 2025)
The shortcut tree routing has been advised to provide near prime routing path as well as maintaining the benefits of the ZigBee tree routing like low memory utility multi-hop routing capacity .But, in spite of the efforts to provide an efficient and reliable protocol, the unicast routing itself has the fundamental limitation in wireless environment due to loose, time period varying, and broadcast way of wireless medium. Such as, even one loose link on a path may result in the miscarriage of end-to-end packet delivery in wireless network setting. In this paper, we propose the rotatory shortcut tree routing that combines shortcut tree routing and rotatory routing. Instead of identifying a next hop node, this rotatory shortcut tree routing allows receiving nodes to compete to forward a packet with the primacy of remaining hops. Because it has acquired advantages of each protocol, it may offer reliable parcel conveyance benefit without any approach for multi-hop routing and forwarder candidate selection for rotatory routing.